1996
DOI: 10.1007/s001050050415
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylsäure als Augmentationsfaktor einer Nahrungsmittel-Allergie

Abstract: A 39-year-old female patient presented with an intense allergic reaction and shock after ingesting sunflower seeds and simultaneously acetylsalicylic acid (ASA). Skin tests and CAP specific. IgE demonstrated an IgE-mediated sensibilization to sunflower seeds. When sunflower seeds were eaten alone, only discrete paresthesia of the oral mucosa occurred. Surprisingly, an oral challenge with ASA was well tolerated. The supplementary contribution of ASA to the allergic reaction was dose-dependent. The quantity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…The finding of an increased sLT production by ethanol in some DBPCFC‐negative patients may be also explained by the possible necessity of an cofactor. The observation that some hypersensitivity reactions are induced only in the presence of cofactors is well known for exercise [18] or drugs [19], but a complex phenomenon involving several mechanisms has also been suggested to play a role in wine‐induced asthma [5]. Although other ingredients of alcoholic beverages such as FAs [4, 6] or cereals (in beer) [7–9] have been shown to elicit adverse reactions, in our patients, FAs were only relevant in the one patient who refused ethanol challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of an increased sLT production by ethanol in some DBPCFC‐negative patients may be also explained by the possible necessity of an cofactor. The observation that some hypersensitivity reactions are induced only in the presence of cofactors is well known for exercise [18] or drugs [19], but a complex phenomenon involving several mechanisms has also been suggested to play a role in wine‐induced asthma [5]. Although other ingredients of alcoholic beverages such as FAs [4, 6] or cereals (in beer) [7–9] have been shown to elicit adverse reactions, in our patients, FAs were only relevant in the one patient who refused ethanol challenge.…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective study from Spain and Portugal showed that nearly 20% of their patients with cold-induced urticaria presented with life threatening reactions to the cold [3]. It is a relatively rare disorder with a reported prevalence of 0.05% as per one study in Europe, with a higher prevalence in northern climates [4]. It is also self-limited, lasting 4–5 years on average.…”
Section: Introductionmentioning
confidence: 99%
“…Möller and colleagues reported a woman who had an attack of anaphylaxis after consuming sunflower seeds and acetylsalicylic acid. Given that in both patients exposure to acetylsalicylic acid alone did not elicit an allergic reaction, and that the triggering foodstuffs alone caused only mild oral allergy syndrome, the authors suggested that acetylsalicylic acid may enhance intestinal absorption of the allergen [7,8]. Matsuo and colleagues showed that, with the combination of wheat and physical exertion or acetylsalicylic acid, serum gliadin levels were significantly higher than when wheat was consumed alone without any other triggering co-factors [9].…”
Section: Acetylsalicylic Acid Dependent Anaphylaxis To Carrots In a Pmentioning
confidence: 99%